Expectation influences the interruptive function of pain: Behavioural and neural findings. (26th August 2016) - Sinke, C.; Schmidt, K.; Forkmann, K.; Bingel, U.
Abstract: Background: Expectations can dramatically influence the perception of pain, as has been shown in placebo analgesia or nocebo hyperalgesia. Here, we investigated the role of expectation on the interruptive function of pain – the negative consequences of pain on cognitive task performance – in 42 healthy human subjects. Methods: Verbal and written instructions were used to manipulate the subjects' expectation of how pain would influence their task performance in an established visual categorization task which was performed with or without concomitant painful thermal stimulation during 3T fMRI scanning. The categorization task was followed by a surprise recognition task. Results: We observed a significant interaction between stimulation (pain/no pain) and expectancy (positive expectation/negative expectation): categorization accuracy decreased during painful stimulation in the negative expectancy group ( N  = 21), while no difference was observed in the positive expectancy group ( N  = 21). On the neural level, the positive expectancy group showed stronger activity in the anterior cingulate cortex (ACC) and hippocampus during painful stimulation compared to the negative group. Moreover, we detected a decrease in connectivity between ACC and fusiform gyrus during painful stimulation in the negative expectancy group, which was absent in the positive expectancy group. Conclusion: Taken together, our data show that expectation can modulate the effect of pain on task performance and that these expectancy effects on the interruptive function of pain are mediated by activity and connectivity changes in brain areas involved in pain processing and task performance. The possibility of changing cognitive task performance by verbal information in clinical population warrants further investigation. Significance: We show that the interruptive function of pain on concurrent visual task performance is influenced by expectation. Positive expectation can abolish the detrimental effects of pain on cognition. These expectancy effects on the interruptive function of pain are mediated by changes in functional connectivity between rostral ACC, posterior fusiform cortex and the hippocampus.